Body image, body composition and environment: do they affect adolescents' physical activity?. (9th March 2022) - Karchynskaya, Viktoryia; Kopcakova, Jaroslava; Madarasova Geckova, Andrea; Klein, Daniel; de Winter, Andrea F; Reijneveld, Sijmen A
Abstract: Background: Most adolescents are less physically active than recommended, despite the strong effort of various stakeholders to promote physical activity (PA). Body image and body composition may play an important role not only in directly facilitating adolescents' PA but also in enabling environment-related factors. As evidence is lacking, we aimed to assess the associations of adolescents' PA with body-related and environment-related factors, whether this differs by age and gender, and whether these factors interact. Methods: We used data on 888 11- to 15-year-old adolescents (mean age = 13.5, 56% boys) from the Health Behaviour in School-aged Children study conducted in 2018 in Slovakia. We used multinomial logistic regression analysis to assess the association of adolescents' PA with body-related factors (body image, body composition) and environment-related factors (PA-promoting environment, less leisure constraints), taking into account age and gender. Results: Adolescents who perceived their body as not too fat were more likely to be physically very active rather than inactive [odds ratios (ORs)/95% confidence interval (CI) 2.15/1.44–3.22], and similarly those who were not overweight/obese (3.24/2.09–5.01) and perceived less leisure constraints (1.74/1.44–2.11). In older adolescents and in girls, the association of adolescents' PA with body composition and environment-related factors was stronger. The association of adolescents' PA with perceiving less leisure constraints was stronger among adolescents who did not perceive their body as too fat (OR/95% CI 1.98/1.26–3.14), and for those who were not overweight/obese (OR/95% CI 1.62/1.01–2.57). Conclusion: Adolescents' PA is associated with both body-related and environment-related factors. These associations are stronger in girls and older adolescents, if co-occurring.